Endometrioid adenocarcinoma of the ovary arising in atypical endometriosis - Terada, Tadashi (e-Century Publishing Corporation, 2012)
Ovarian endometriosis can transform into malignant tumors, and ovarian carcinomas relatively frequently contain foci of endometriosis. In this study, the author reviewed 15 cases of endometrioid adenocarcinoma of the ovary in the last 15 years of our pathology laboratory in search for the presence of endometriosis within the tumor. Six (40%) of the 15 endometrioid adenocarcinoma were found to have endometriosis in the tumor. All of the endometriosis were atypical. The age of the 6 patients ranged from 44 year to 78 year with a median of 59 years. Grossly, the endometrial adenocarcinomas with endometriosis were characterized by unilocular cystic tumors in 5 cases and multilocular cystic tumor in one case. Histologically, the grade of endometrioid carcinoma was grade I in 3 cases, grade II in 2 cases and grade III in 1 case. Endometriosis was mixed with the tumors or was present adjacent to the tumor. The endometriosis was composed of a layer of atypical epithelium (atypical endometriosis), and gradual merges between endometriosis and carcinoma were present in 3 cases. These findings suggest that atypical endometriosis can transform into endometrioid carcinoma.